Output calculation of electron therapy at extended SSD using an improved LBR method. Issue 2 (14th January 2015) - Alkhatib, Hassaan A.; Gebreamlak, Wondesen T.; Tedeschi, David J.; Mihailidis, Dimitris; Wright, Ben W.; Neglia, William J.; Sobash, Philip T.; Fontenot, Jonas D.
Abstract : Purpose: To calculate the output factor (OPF) of any irregularly shaped electron beam at extended SSD. Methods: Circular cutouts were prepared from 2.0 cm diameter to the maximum possible size for 15 × 15 applicator cone. In addition, two irregular cutouts were prepared. For each cutout, percentage depth dose (PDD) at the standard SSD and doses at different SSD values were measured using 6, 9, 12, and 16 MeV electron beam energies on a Varian 2100C LINAC and the distance at which the central axis electron fluence becomes independent of cutout size was determined. The measurements were repeated with an ELEKTA Synergy LINAC using 14 × 14 applicator cone and electron beam energies of 6, 9, 12, and 15 MeV. The PDD measurements were performed using a scanning system and two diodes—one for the signal and the other a stationary reference outside the tank. The doses of the circular cutouts at different SSDs were measured using PTW 0.125 cm 3 Semiflex ion‐chamber and EDR2 films. The electron fluence was measured using EDR2 films. Results: For each circular cutout, the lateral buildup ratio (LBR) was calculated from the measured PDD curve using the open applicator cone as the reference field. The effective SSD (SSDeff ) of each circular cutout was calculated from the measured doses at different SSD values. Using the LBR value and the radius of the circular cutout, the corresponding lateral spread parameter [ σR ( z )] was calculated. Taking the cutout size dependence of σR ( z ) into account, the PDD curves of the irregularly shaped cutouts at the standard SSD were calculated. Using the calculated PDD curve of the irregularly shaped cutout along with the LBR and SSDeff values of the circular cutouts, the output factor of the irregularly shaped cutout at extended SSD was calculated. Finally, both the calculated PDD curves and output factor values were compared with the measured values. Conclusions: The improved LBR method has been generalized to calculate the output factor of electron therapy at extended SSD. The percentage difference between the calculated and the measured output factors of irregularly shaped cutouts in a clinical useful SSD region was within 2%. Similar results were obtained for all available electron energies of both Varian 2100C and ELEKTA Synergy machines.